Audels new electric library for engineeers, electricians : all electrical workers, mechanics and students - Graham, Frank Duncan (New York : T. Audel & Co., 1929)
It presents the fundamental principles, rules and applications of applied electricity.
The volumes are frequently revised.
occ 15/01/2019
Reference
Keywords: Electrical engineering